PENGARUH RASIO KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN BUMN NON-KEUANGAN DI BURSA EFEK INDONESIA - Azmy, Ahmad; Vitriyani, Vitriyani (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2019)
This study aims to determine the effect of the Financial Performance Ratio on the value of non-financial BUMN companies that are publicly listed on the Indonesia Stock Exchange. The data used are financial statements for 5 years starting from January 2012 to December 2016. This research is included in the association research which is to find out the effect of the independent variables on firm value. This research based on the results of testing the hypothesis partially on the T-Test, shows that Return On Assets (ROA) and Earning Per Share (EPS), affect the value of the company, while the Debt to equity ratio (DER) and Price Earning Ratio (PER) do not affect the value of the company. The results of the research in testing the hypothesis simultaneously on the F-Test show that the independent variables influence the value of the company.